The Unreliable Narrator in Ahmed Saadawi’s Frankenstein in Baghdad - Abdulkadhom Abdulridha, Sabrina; Raad Kareem Abd-Aun, (Advances in Humanities and Contemporary Studies, 2021)
Narration is a complex literary concept that has been discussed and elaborated on by many literary critics and thinkers for decades. Ever since the conceptualization of the term “the unreliable narrator,” critics have come forward to mark the many possibilities were narrators may be confirmed to be unreliable, depending on flaws or certain defining markers that indicate unreliable characteristics within the literary work. This paper shall confine the means of the unreliable narrator and finalize its distinct characteristics in several points. Narrators should be tested in means of the stability of their personality, the reality of their given statements and their accordance with the implied author. Any unmistakable shortcoming will naturally affect the reliability of the narrator. The means of the unreliable narrator shall be studied thoroughly in Ahmad Saadawi's award-winning novel Frankenstein in Baghdad (2013) and the reliability of the narrators will be evaluated according to the proposed points.